Thiol-functionalized ZrP reinforced poly(MMA-co-MI) nanocomposites: High optical transparency and superior thermal stability for optical coatings - Shahrzad Jahangiri; Samira Sarikhani (PLoS ONE, 2026)
This study presents novel transparent and thermally stable nanocomposites based on poly(methyl methacrylate-co-N-2-methyl-4-nitrophenylmaleimide) (P(MMA-co-MI)) reinforced with thiol-functionalized zirconium phosphate (ZrP-SH) nanofillers. The key innovation is the thiol modification of ZrP, which enhances interfacial interactions and ensures uniform dispersion at low loadings (≤1 wt%). The nanocomposites were prepared through solution blending and characterized using FTIR, XRD, SEM, TEM, TGA, DSC, and UV-Vis spectroscopy. Compared to the neat copolymer, the nanocomposites demonstrated an approximately 30 °C increase in glass transition temperature (from 164.3 °C to 168.4 °C) and an increase in onset degradation temperature from 265 °C to about 297 °C while maintaining high optical transparency in the visible range at low filler contents. These silicon-free materials effectively address the trade-off between thermal stability and optical clarity, offering significant potential for advanced optical coatings, sensors, protective layers, and optoelectronic packaging applications.